Enhancing pediatric endodontic treatment: Intraosseous anesthesia with computer-controlled delivery system - Suciati, Khomsah; Indriyanti, Ratna; Gunawan, Kirana Lina (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Pain control during endodontic treatment is essential but challenging, particularly in pediatric dentistry. Intraosseous anesthesia (IO) ensures adequate areas are anesthetized for endodontic treatment of the primary tooth with only a single injection site and a small amount of anesthetic solution required. Anesthesia should be delivered slowly to enhance the success rate, minimize pain and, for the IO technique, minimize risk of osteonecrosis. The IO anesthesia delivery system that meets such criteria is computer-controlled local anesthetic delivery (CCLAD). Purpose: To describe the enhancement of pediatric endodontic treatment with minimum risk intraosseous anesthesia using CCLAD. Case: An 8-year-old male patient came to the Pediatric Dentistry Clinic at Padjadjaran University Dental Hospital reporting pain on the lower right second molar deciduous teeth, indicated for vital pulpectomy. Case Management: The procedure of vital pulpectomy was done under local anesthesia. Patient was given intraosseous injection with CCLAD prior to opening access. The point of injection was at two mm apical from distal interdental papillae of the lower right second molar deciduous teeth. The patient remained calm throughout the local injection and vital pulpectomy procedure. Conclusion: Intraosseous anesthesia is beneficial when used for pain control during pediatric endodontic therapy. The use of CCLAD gives comfort to the patient while lowering the risk of necrotizing alveolar bone.